Explorer : the mystery boxes (New York : Amulet Books, 2012)
An anthology of short graphic works by such artists as Kazu Kibuishi, Dave Roman, and Raina Telgemeier, all on the theme of a mysterious box and the marvels, or mayhem, inside.
Accelerated Reader AR
Keywords: Boxes -- Juvenile fiction; Children's stories, American; Graphic novels; Boxes -- Fiction; Short stories; Graphic novels